Therapeutic potential of second degree's skin burns by topical dressing of Teucrium ramosissimum that promotes re‐epithelialization. Issue 5 (14th March 2022) - Guesmi, Fatma; Saidi, Issam; Abbassi, Raoudha; Saidani, Mabrouka; Hfaiedh, Najla; Landoulsi, Ahmed
Abstract: The aim of the report is to assess the protective effect of powder aerial part of Teucrium ramosissimum (TS) on the in vivo wound‐healing of second‐degree burn injuries. Teucrium phytocompounds were characterized by FTIR, HPLC, and GC/MS spectra. Burn wound models were employed to evaluate the in vivo wound‐healing activity. Thirty six wistar rats with burn wounds were divided into six groups and treated daily with TS, the mixture of Teucrium and honey (TS‐HY), thymol and Dermosalic® (0.05%) (DS) creams. Skin epithelialization was monitored on the 4th, 13th, and 21st days. Proteins and the level of malondialdehyde in the burned skin were assessed. Microscopic and macroscopic investigations of skin wound tissues showed significant wound closure rate via complete epidermal reepithelization and regeneration, higher protein content, collagen synthesis and deposition, hair follicles growth post wounding that were promoted in TS‐, thymol‐, TS‐HY‐ and DS‐treated wound tissues compared to the untreated burned wound tissues that was characterized by the absence of the epithelialization, vascularization and the formation of the epidermis layer. Additionally, the skin healing potential of TS and TS‐HY was validated by markedly decreased of lipid peroxidation. Overall, TS was found to possess complete wound closure and improves the healing process.